Modelling and Simulation of the Immune Process at Viral Hepatitis C - Edisonov, I.; Ranchev, S. (International Journal For Research In Mathematics And Statistics, 2019)
Mathematical model at viral hepatitis C is proposed as nonlinear system from ordinary differential equations. Based on clinical data of the immune process at viral Hepatitis C a numerical simulation is carried out. As a result of the simulation such values of the parameters in the kinetic model are obtained at which the experimental clinical values are maximal near to the theoretical results.